Hubungan Merokok, Diabetes Melitus Terhadap Kejadian Katarak pada Pasien Berobat di Rumah Sakit Mata - Ariska Setia Putri; Endro Pranoto; Baiq Novaria Rusmaningrum; Raden Gunawan Effendi (Jurnal Health Sains, 2023)
Cataracts are an eye disorder characterized by clouding of the eye lens which can interfere with vision. Cataracts are the cause of at least 50% of blindness cases worldwide. As life expectancy increases, the number of affected respondents increases. Cataracts can be caused by intrinsic factors and extrinsic factors. This study aims to find out the relationship of smoking and diabetes mellitus with the occurrence of the cataract in patient treatment at the West Nusa Tenggara Provincial Eye Hospital. This study is observationally analytical using cross-sectional design. The sampling technique is porpusive sampling. The research sampel consisted of 110 samples that fit the inclusion and exclusion criteria. The result of this study were obtained smoking are 59 (53,6%) and who were not smoking 51 (46,4%). While respondents with diabetes mellitus 54 (49,1%) and who were not diabetes mellitus 56 (50,9%). There is relationship between smoking with incidence of cataract in patients treatment with p-value 0,038 and with PR 2,236 more at risk of cataract and there is relationship between diabetes mellitus with the incidence of cataract in patients treatment with p-value 0,002 and with PR 3,316more at risk of cataract. There is significant relationship between smoking and diabetes mellitus in patients treatment at the west nusa tenggara provincial eye hospital.